The use of a landscape perspective to assess the nature value of a traditionally managed landscape - Poudel, Parbakhar (2010)
Loss of biodiversity related with diminishing traditional land use practice has raised global concern. Since, traditional land use practices is socio-economically unviable, many incentive based conservation approaches have emerged in order to encourage practitioners to continue with their practices. High nature value farmland is one of the newly emerged conservation approaches which aim at identifying causalities between farming type and biodiversity, and for providing support to the farming types which contribute to maintenance of biodiversity. Determination of the basis for the support is the major challenge, specifically the indicators used and the spatial extents taken into consideration.